EFEK PEREKAT PADA BRIKET BERBAHAN BAKU AMPAS PATI ONGGOK - , YUDIA TIRTA K, Rachmawan Budiarto, S.T, M.T ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, the energy crisis is one of the important problems in Indonesia. Supply of fuel oil (BBM) and LPG are lower than the level of consumption. Therefore, the price of fuel increases by the time, as well as the impact on several other sectors. Margoluwih Village, Klaten regency has 25 starch industries producing flour with a total production Â± 50 tons of flour per day and 17.5 tons of waste. Waste of starch sugar is a kind of biomass waste. It is very potential to create briquettes production. In this research, the type of adhesive used is cassava starch and tar, which the compositions are 45.57 ml, 51 ml and 60.71 ml. The results showed that the difference type of adhesive gives a big effect on calories of briquettes, moisture, ash contain, volatile matter and fixed carbon. Briquettes with tar adhesive as much as 60.71 ml has the highest calories of 6590 cal/g, but the volatile matter does not fulfill standard of SNI, beside that, the smoke color of combustion product is black and foul-smelling. The best quality briquettes based on physical, chemical and economic analysis is briquette with 45.57 ml of cassava starch adhesive. It shows potential on economic feasibility as long as the briquette can fulfill standard of SNI. Briquette with initial capital Rp.155,673,315 interest rates of 14% for 5 years, earned profit per month is Rp 11,935,474 assuming briquette sales of Rp 3,500/kg and liquid smoke Rp 8,000/l